2023
DOI: 10.1111/joor.13571
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronic acid injections for pain relief and functional improvement in patients with temporomandibular disorders: An umbrella review of systematic reviews

Francesco Agostini,
Martina Ferrillo,
Andrea Bernetti
et al.

Abstract: BackgroundTemporomandibular disorders (TMD) are the main cause of chronic facial pain, and intra‐articular (IA) injections of hyaluronic acid (HA) are commonly performed.ObjectivesThis umbrella review of systematic reviews aimed at analysing the effectiveness of HA injections on pain and functional outcomes in patients affected by TMD.MethodsPubMed, Cochrane Library and PEDro were systematically searched from inception until 17 January 2023 to identify systematic reviews evaluating the effects on pain and func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 64 publications
0
20
0
Order By: Relevance
“… 55 Some scholars have studied the effect of Hyaluronic Acid (HA), Corticosteroids (CS) or Platelet-rich Plasma (PRP) injected at the time of lavage on the rehabilitation of patients. 56 The results show that there is no difference in the rehabilitation outcome after 2 years between the addition of HA or CS and the simple lavage, but it can reduce pain and inflammation for a month to 3 months after the irrigation is completed. 35 At the same time, some scholars have proposed that intra-articular steroid injection after surgery, although there is a trend of improvement, its therapeutic response is very dependent on the patient’s own conditions and is affected by many variables, so it is not the best method to use.…”
Section: Analgesics Used During the Irrigationmentioning
confidence: 88%
“… 55 Some scholars have studied the effect of Hyaluronic Acid (HA), Corticosteroids (CS) or Platelet-rich Plasma (PRP) injected at the time of lavage on the rehabilitation of patients. 56 The results show that there is no difference in the rehabilitation outcome after 2 years between the addition of HA or CS and the simple lavage, but it can reduce pain and inflammation for a month to 3 months after the irrigation is completed. 35 At the same time, some scholars have proposed that intra-articular steroid injection after surgery, although there is a trend of improvement, its therapeutic response is very dependent on the patient’s own conditions and is affected by many variables, so it is not the best method to use.…”
Section: Analgesics Used During the Irrigationmentioning
confidence: 88%
“…LMW‐HA promotes M1 macrophage polarization, 24 while HMW‐HA attenuates synovitis by promoting M2 macrophage polarization 25 . It has been demonstrated that HMW‐HA is effective in the treatment of TMJ inflammation in animal experiments 26 and clinical 27 . However, the relationship of HA, ALPK1 and macrophage polarization in TMJ synovitis remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“… 25 It has been demonstrated that HMW‐HA is effective in the treatment of TMJ inflammation in animal experiments 26 and clinical. 27 However, the relationship of HA, ALPK1 and macrophage polarization in TMJ synovitis remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Conservative strategies should be advocated as the primary approach for the initial treatment of TMDs, covering physical therapies, self‐management with disease elucidation, occlusal splint therapy and psychological interventions 6 . Additional therapeutic strategies, such as intra‐articular injections of hyaluronic acid and plasma‐rich platelets, have demonstrated efficacy in alleviating pain and improving functionality among patients with TMDs 7 . Despite these therapeutic advancements, the aetiology of TMDs remains incompletely elucidated, underscoring the ongoing need for further exploration 1…”
Section: Introductionmentioning
confidence: 99%